TCM “medicine and food homology” in the management of post-COVID disorders - Ng, Chester Yan Jie; Bun, Hung Hung; Zhao, Yan; Zhong, Linda L. D. (Frontiers in Immunology, 2023)
Background: The World Health Organization declared that COVID-19 is no longer a public health emergency of global concern on May 5, 2023. Post-Acute Sequelae of COVID-19 (PASC), often referred to as Post-COVID disorders or "Long-COVID," are, however, becoming more common. Hence, there lies a growing need to develop safe and effective treatment measures to manage post-COVID disorders. Investigating the use of TCM medicinal foods in the long-term therapy of post-COVID illnesses may be beneficial given contemporary research's emphasis on the development of medicinal foods.The use of medicinal foods for the long-term treatment of post-COVID disorders is highlighted in this review. Following a discussion of the history of the TCM "Medicine and Food Homology" theory, the pathophysiological effects of post-COVID disorders diseases will be briefly reviewed. An analysis of TCM medicinal foods and their functions in treating post-COVID disorders will then be provided before offering some insight into potential directions for future research and application.Key Findings and Discussion: TCM medicinal foods can manage different aspects of post-COVID disorders. The use of medicinal foods in the long-term management of post-COVID illnesses may be a safe and efficient therapy choice because they are typically milder in nature than chronic drug use. These findings may also be applied in the long-term post-disease treatment of similar respiratory disorders.